Diffusion-Sensitized Ophthalmic Magnetic Resonance Imaging Free of Geometric Distortion at 3.0 and 7.0 T. Issue 5 (May 2015) - Paul, Katharina; Graessl, Andreas; Rieger, Jan; Lysiak, Darius; Huelnhagen, Till; Winter, Lukas; Heidemann, Robin; Lindner, Tobias; Hadlich, Stefan; Zimpfer, Annette; Pohlmann, Andreas; Endemann, Beate; et al.
<x xml:space="preserve">Abstract</x> Objectives This study is designed to examine the feasibility of diffusion-sensitized multishot split-echo rapid acquisition with relaxation enhancement (RARE) for diffusion-weighted ophthalmic imaging free of geometric distortions at 3.0 and 7.0 T in healthy volunteers and patients with intraocular masses. Materials and Methods A diffusion-sensitized multishot split-echo RARE (ms-RARE) variant is proposed as an alternative imaging strategy for diffusion-weighted imaging. It is compared with standard single-shot echo planar imaging (EPI) and readout-segmented EPI in terms of geometric distortions in a structure phantom as well as in vivo at 3.0 and 7.0 T. To quantify geometric distortions, center of gravity analysis was carried out. Apparent diffusion coefficient (ADC) mapping in a diffusion phantom was performed to verify the diffusion sensitization within ms-RARE. An in vivo feasibility study in healthy volunteers (n = 10; mean age, 31 ± 7 years; mean body mass index, 22.6 ± 1.7 kg/m2) was conducted at 3.0 and 7.0 T to evaluate clinical feasibility of ms-RARE. As a precursor to a broader clinical study, patients (n = 6; mean age, 55 ± 12 years; mean body mass index, 27.5 ± 4.7 kg/m2) with an uveal melanoma and/or retinal detachment were examined at 3.0 and 7.0 T. In 1 case, the diseased eye was enucleated as part of the therapy and imaged afterward with magnetic resonance microscopy at 9.4 T. Macrophotography and histological investigation was carried out. For qualitative assessment of the image distortion, 3 independent readers reviewed and scored ms-RARE in vivo images for all subjects in a blinded reading session. Statistical significance in the difference of the scores (a) obtained for the pooled ms-RARE data with b = 0 and 300 s/mm2 and (b) for the 3 readers was analyzed using the nonparametric Mann-Whitney test. Results The assessment of geometric integrity in phantom imaging revealed the ability of ms-RARE to produce distortion-free images. Unlike ms-RARE, modest displacements (2.3 ± 1.4 pixels) from the fast low angle shot imaging reference were observed for readout-segmented EPI, which were aggravated for single-shot EPI (8.3 ± 5.7 pixels). These observations were confirmed in the in vivo feasibility study including distortion-free diffusion-weighted ophthalmic images with a 0.5 × 0.5 × 5 mm3 spatial resolution at 3.0 T and as good as 0.2 × 0.2 × 2 mm3 at 7.0 T. The latter represents a factor of 40 enhancement in spatial resolution versus clinical protocols recently reported for diffusion-weighted imaging of the eye at 1.5 T. Mean ADC values within the vitreous body were (2.91 ± 0.14) × 10−3 mm2/s at 3.0 T and (2.93 ± 0.41) × 10−3 mm2/s at 7.0 T. Patient data showed severe retinal detachment in the anatomical images. Whereas the tumor remained undetected in T1-weighted and T2-weighted imaging at 3.0/7.0 T, in vivo ADC mapping using ms-RARE revealed the presence of a uveal melanoma with a significant contrast versus the surrounding subretinal hemorrhage. This observation was confirmed by high-resolution ex vivo magnetic resonance microscopy and histology. Qualitative analysis of image distortion in ms-RARE images obtained for all subjects yielded a mean ± SD image quality score of 1.06 ± 0.25 for b = 0 s/mm2 and of 1.17 ± 0.49 for b = 300 s/mm2. No significant interreader differences were observed for ms-RARE with a diffusion sensitization of b = 0 s/mm2 and 300 s/mm2. Conclusions This work demonstrates the capability of diffusion-sensitized ms-RARE to acquire high-contrast, high–spatial resolution, distortion-free images of the eye and the orbit at 3.0 and 7.0 T. Geometric distortions that are observed for EPI-based imaging approaches even at lower field strengths are offset by fast spin-echo–based imaging techniques. The benefits of this improvement can be translated into the assessment of spatial arrangements of the eye segments and their masses with the ultimate goal to provide guidance during diagnostic treatment of ophthalmological diseases.